Obstetric Violence - Maravall Buckwalter, Isabel (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
The concept of «obstetric violence» is recognized internationally, though it lacks a definitive and universally accepted definition. This indicates that, while some consensus exists, debates and uncertainties remain regarding its precise meaning and scope. This article explores the evolution of international definitions of obstetric violence, breaking down its key elements and examining the controversies surrounding its use. It concludes by reflecting on the main challenges posed by current definitions and their broader implications.